Inflamm-ageing and senescence in gout: the tale of an old king’s disease. - Vazirpanah, Nadia; R.D.J. Radstake, Timothy; C.A. Broen, Jasper (Current Aging Science, 2015)
Gout is the most common auto-inflammatory arthritis that leads to severe comorbidities such as cardiovascular diseases, renal impairment and metabolic disorders at an early age. We hypothesize that chronic as well as frequent flares of intermittent inflammation, caused by uric acid contribute to an early onset of cardiovascular-, renal- and metabolic diseases. Persistent exposure of the cells to such inflammatory events elaborates DNA damage, excessive cell turnover inconsistent with age and telomere shortening which is representative for accelerated senescence. In this review we aim to untangle the intriguing effect of inflammation-induced cellular senescence on the high prevalence of age-related cardiovascular, renal and metabolic diseases in gout.
Keywords: DNA damage